ØªØ£Ø«ÙŠØ± ØªØ¹Ù„ÙŠÙ… ÙƒØªØ¨ Ø§Ù„ØªØ±Ø§Ø« ÙÙŠ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© - Muhammad Syarifuddin; Baiq Laili Rahmawati; Sudi Yahya Husein (Lughatu Ad-dhat, 2023)
The purpose of this research is to define the effect of teaching heritage books on the reading skill of students of Class B of the Mataram State Islamic University Institute. The population in this research is all students in the university institute whose sample is the B class of twenty students. To collect the data, the researcher used the test, the interview, and the questionnaire. As for analyzing it, the researcher used the regression symbol and the correlation coefficient. Based on the results of analyzing the data with the two symbols, the researcher found that the relationship between the two variables is positive and very important at the level of significance 0.05, and this indicates that there is a relationship between the two variables. As for the percentage of teaching heritage books in reading skill by regression symbol, it is 24.8%. Therefore, the researcher deduced that the wonderful hypothesis, which says, "There is an effect of teaching heritage books on the reading skill of students of class B, Mataram State Islamic University Institute," is acceptable, and the hypothesis 0, which says, "there is no effect of teaching heritage books on the reading skill of students of class B." Mataram State Islamic University Institute " Rejected. Keywords: heritage books, reading skill